(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Solutions to the problems of improving the population’s health do not lose their relevance. The emphasis made on the prevention and treatment of obesity, cardiovascular diseases, on the reduction of cardiac mortality contributed to the development of differentiated preventive measures. The concept of "Metabolic Syndrome" has combined into a single complex interdependent metabolic disorders that form the basis of the pathogenesis of various diseases (atherosclerosis, hypertension, ischemic heart disease, obesity, type 2 diabetes mellitus, etc.). The possibilities of preventing and treating each of the diseases that make up the metabolic syndrome are determined by the success of the prevention and treatment of the metabolic syndrome itself.